User Centered Design Approach for Developing a Health Monitoring System for Posyandu - Okta Ramma Saputri; Hanifah Permatasari; Vihi Atina (Komunitas Dosen Indonesia, 2025)
Indonesia continues to report high maternal and infant mortality rates, underscoring the urgent need for effective community-based health information systems, particularly in rural areas served by Posyandu (Integrated Health Service Posts). Despite their crucial role in primary healthcare delivery, many Posyandu still rely on manual data recording, resulting in fragmented documentation, delayed health risk detection, and inefficient decision-making processes. This study adopts a design research approach, utilizing the User-Centered Design (UCD) methodology to develop a web-based health monitoring system tailored for non-technical users, specifically Posyandu cadres in Dukuh Village, Boyolali Regency. The UCD process involved four iterative stages: understanding the user context, specifying user requirements, designing high-fidelity interface prototypes using Figma, and conducting usability evaluation through the System Usability Scale (SUS). The developed prototype includes key features such as digital patient data entry, real-time health examination input, visual health monitoring graphs, and automatic report generation by category and period. Usability testing was conducted with five Posyandu cadres who participated in defined usage scenarios and completed the SUS questionnaire. The resulting average SUS score was 84, categorized as “Excellent,” indicating that the system is intuitive, accessible, and efficient for users with limited technological experience. These findings demonstrate that the UCD approach effectively aligns system functionality with user needs, enhancing usability and supporting timely, data-driven health service decisions. This model offers significant potential for scalability and adaptation in other Posyandu settings, contributing to more integrated and responsive public health interventions at the village level.